Letermovir treatment of cytomegalovirus infection or disease in solid organ and hematopoietic cell transplant recipients. Issue 4 (20th July 2021) - Linder, Kathleen A.; Kovacs, Christopher; Mullane, Kate M.; Wolfe, Cameron; Clark, Nina M.; La Hoz, Ricardo M.; Smith, Jeannina; Kotton, Camille N.; Limaye, Ajit P.; Malinis, Maricar; Hakki, Morgan; Mishkin, Aaron; et al.
Abstract: Background: Few options are available for cytomegalovirus (CMV) treatment in transplant recipients resistant, refractory, or intolerant to approved agents. Letermovir (LET) is approved for prophylaxis in hematopoietic cell transplant (HCT) recipients, but little is known about efficacy in CMV infection. We conducted an observational study to determine the patterns of use and outcome of LET treatment of CMV infection in transplant recipients. Methods: Patients who received LET for treatment of CMV infection were identified at 13 transplant centers. Demographic and outcome data were collected. Results: Twenty‐seven solid organ and 21 HCT recipients (one dual) from 13 medical centers were included. Forty‐five of 47 (94%) were treated with other agents prior to LET, and 57% had a history of prior CMV disease. Seventy‐seven percent were intolerant to other antivirals; 32% were started on LET because of resistance concerns. Among 37 patients with viral load < 1000 international units (IU)/ml at LET initiation, two experienced >1 log rise in viral load by week 12, and no deaths were attributed to CMV. Ten patients had viral load > 1000 IU/ml at LET initiation, and six of 10 (60%) had a CMV viral load < 1000 IU/ml at completion of therapy or last known value. LET was discontinued in two patients for an adverse event. Conclusions: Patients treated with LET with viral load < 1000 IU/ml had good virologic outcomes. Outcomes were mixed when LET was initiated at higher viral loads. Further studies on combination therapy or alternative LET dosing are needed.